Formas de relevo e dinâmica costeira em São Caetano de Odivelas (PA) - PICANÇO, Maria do Socorro Monteiro (Universidade Federal do Pará, 2017)
The present research was conducted on the northern part of municipality of São Caetano de Odivelas (PA), which had as objectives identify the relief units, analyze the distribution of these units from the physiographic conditions, verify the variation of multitemporal position of the coastline, identify the geoindicators and analyze the consequences for the vegetation and the morphology that area of study. The methodological procedures of the research included the bibliographical survey and literature review, cartographic base survey and products from remote sensors; treatment and digital processing of orbital images, thematic mapping and field work. Among the morphological units, in this area of study, are the tabuleiros that totals of 52.7 km ² and are located in the center of this area of study, in the shape of isolated blocks with a wavy soft relief, where the altimetry ranges from 6 to 30 meters; The plains of muddy tidal add up to 95.9 km ² and will position themselves as sites parallel to the coastline and along the lower course of rivers, have a flat topography, in which his altimetry goes 2 to 6 meters; muddy banks of intertidal have 7.3 km ², are positioned so as planes parallel to the coastline, with slightly angled relief that goes 0 to 2 meters; the sand ridges subatual add up to 2.2 km ² and are positioned in the shape of arrows arranged as meaning of the present coastline, with flat topography, with a altimetry 6 to 12 meters; alluvial plains have 10.7 km ² and are situated in contact with mangrove areas and along some river channels, with flat topography, above 6 meters; alluvial plains presenting species of Avicennia sp. have 1.1 km ², feature a flat topography that goes 2 to 6 meters and are found the interior plains of muddy tidal; alluvial plains with vegetation fields add up to 4.4 km ², are located shaped places of the narrow valley floors with a flat topography ranges from 4 to 10 meters; the sandy bars have 17.3 km ², are located as deposits elongated in the sense of the mouths of estuaries and feature a flat topography, which ranges from 0 to 2 meters. The geomorphological indicators identified are the advance and retreat of the coastline; the emergence and growth of sandy bars; approach and retraction of sandy bars in relation to the coastline; the biological indicators relates to formation and destruction of neossolos mangrove soil; the increase of mangrove area and development of the standard "Escada"; reduction mangrove area and pattern formation "Paliteiro". The morphological changes can be classified in their majority as acrecionais because in 24 years there was an increase in mangrove area of 3.85 km ², which responsible for 4.19% of the total area plus in addition to have occurred in this period, installing two new islands, the Nova and Peruru. The dynamic that occurs in this municipality cause changes in soil and morphology due to installation of neossolos and formation of mangrove ecosystem, besides the occurrence of patterns "Escada" and "Paliteiro".